(untitled) (World Bulletin of Physical Education and Sports Science, 2026)
This article presents the theoretical and methodological foundations for modeling the structure and content of training for highly qualified boxers. The study analyzes issues related to effective management of the process of improving sports mastery, the formation of the motivational sphere, and the organization of the training process based on a personality-oriented approach. The conceptual provisions of the model are substantiated, including a holistic approach to sports training, ensuring the unity of general and special physical training with technical-tactical preparation, the introduction of feedback and correction mechanisms, and reliance on the principle of variability. The developed model contributes to the improvement of the sports training system of elite boxers and to the enhancement of competitive performance.